IMPROVING CONTINUOUS QUALIFICATION OF TEACHERS OF SPORTS EDUCATIONAL INSTITUTIONS AS A PEDAGOGICAL PROBLEM (TAMADDUN NURI JURNALI, 2024)
This article talks about the system of training of teachers of sports educational institutions, the current issues of organization of the process of their continuous training.